Undrained strength of clay determined from simple shear test - Huang, Bin; Cai, Shiqian; Li, Jingjing; Wu, Kunming; Yang, Wenhui (Frontiers in Earth Science, 2023)
Undrained shear strength of clay is an important parameter for design of embankment, shallow foundation and pile foundation. Among various test methods of undrained strength, the simple shear is sometimes more essential, such as the mode of shearing of the soil surrounding the pile is very similar to that in a simple shear test. This study employs a series of undrained strength tests with Berkeley simple shear apparatus. Three reconstituted natural clays and one artificial clay were tested with a range of coefficient of consolidation. The influence factors, including sample pre-consolidation pressure, saturation back pressure, shearing rate, height of specimen, consolidation stress and lateral stress ratio, were investigated in undrained simple shear tests. The failure mode in simple shear and corresponding strength parameters are also examined. Based on test dataset, models for describing the undrained strength with simple shear for clays of high plasticity are developed, and compared to test data for normally consolidated reconstituted clay. Good agreement between models and intact Onsoy clay is also observed when allowance is made for coefficient of consolidation and strength parameters of undisturbed clay and in situ stress state.